Strategi Komunikasi Bank Indonesia dalam Kampanye Mositande Masugi Ngata pada Pengendalian Inflasi Sulteng - Safitri, Nur; Lampe, Ilyas; Herawati, Andi Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This research focuses on the Mositande Masugi Ngata (Let's Synergize to Control Inflation) campaign, which aims to analyze the communication strategy implemented by BI Central Sulawesi by utilizing cultural strengths to support inflation control. This research is based on the communication strategy theory based on the Harold D Lasswell paradigm with a qualitative approach based on case studies. The results of the research show that BI Central Sulawesi's communication strategy in the Mositande Masugi Ngata campaign is carried out through five main stages: (1) Identification of Stakeholders and Their Roles (who), (2) Development of Local Wisdom- Based Themes (says what), (3) Selection of Communication Channels (in which channel), (4) Implementation of Campaign Communication (to whom), and (5) Campaign Evaluation (with what effect). The application of local wisdom principles is a key element in building campaign messages that are relevant to the local community's culture in strengthening coordination between stakeholders, while creating more effective communication.